L’état sanitaire des premiers aménagements de berge en bois antiques de Saint-Lupien à Rezé/Ratiatum (Loire-Atlantique) : l’apport de la xylo-entomologie - Magali Toriti; Aline Durand; Fabien Fohrer (Gallia)
The contribution of entomology to xylological analyses is a new and increasingly common approach in the field of heritage preservation. Such an approach was adopted for the study of waterlogged wooden pieces such as piles and stakes stemming from the earliest embankments in the Saint Lupien quarter at Rezé/Ratiatum (Loire-Atlantique). This method makes it possible to identify xylophagous insects based on the traces they left in the wood, i.e., galleries and excreta of the xylophagous larvae. The analysis of traces makes this approach very different from a sedimentological entomological study, based rather on the remains of insects (elytra). An identification key of these traces, developed as part of a doctoral thesis, was tested on the wooden pieces used at Saint-Lupien (piles and stakes) and made it possible to identify three groups of xylophagous insects. As each insect has a particular biology, their sometimes precise species identification provides valuable insights into the nature of the wood and helps to evaluate its state of preservation and to determine the moment when it was infested. These data are completed by the observations usually carried out on wooden pieces such as the specific anatomy of the wood species, the particularities of the tree (knots, preserved sapwood, presence of bark, scarring ring, etc.), the shape of the wood cut and any possible tool marks. The interpretation of the archaeological data, enhanced by this new type of analysis thus benefits from valuable insights into the selection and use of timber by the riverside communities in Roman times and to some extent reveals the condition of the supply forest.